Od Harmela do Ouimeta – przedsiębiorczość etyczna w praktyce - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2014)
The article presents an analysis with the method of phenomenological praxeology of two concepts of entrepreneurship: the nineteenth-century concept of Leon Harmel and that of J.-Robert Ouimet. The ontological-ontic coherence functions as the main practical directive of phenomenological praxeology, according to which it is necessary to preserve the ontological-ontic coherence of management in order to ensure the high efficiency of an enterprise and high level of ethics in its command structures. The analysis leads to the conclusion that Harmel’s and Ouimet’s concepts, based on promoting dignity and servant leadership, ensure the ontological--ontic coherence of management and can be seen as a model (as a paradigm) of ethical entrepreneurship.